DEVELOPMENT OF E-BUSINESS TOWARDS LABOR MARKET FOR HIGHER EDUCATION - Mubdik, M. Ahsanul; W, Delliana Eka; Kurniawan, Fachrul (Letters in Information Technology Education (LITE), 2018)
The internet business is used for information exchange, product catalogs, promotional media, e-mails, bulletin boards, electronic questionnaires, and mailing lists. The internet can also be used to dialogue, discuss, and consult with consumers online, so that consumers can be involved proactively and interactively in the design, development, marketing, and sale of products. By using the internet, we can run an electronic business or commonly called e-business as a means of expanding employment opportunities. Given the smaller quota to find employment, that ebusiness is the right solution for college graduates.